THE FORMATION OF THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE HISTORY OF EVERYDAY LIFE AND LIVELIHOODS OF THE SOCIETY IN HISTORICAL SCIENCE - G. N. Rykun; E. V. Karapetyan (Гуманитарные и юридические исследования)
The article reveals the genesis, the origins of the formation and evolution of the history of everyday life and the livelihoods of the society as an independent direction in history. Shows the attitude to the problem of foreign and domestic researchers, are determined by its differences from the related branches of historical knowledge. The authors emphasize the significance of studying this problem in historical perspective at the most challenging, critical stages of social evolution. The paper presents a detailed analysis of approaches to the problems of everyday life of German researchers, whose experience influenced the attitude of the representatives of the national historical school to the history of everyday life. This emphasizes the regionalization process research practices in the direction in question in the Russian context. According to the authors, this trend is due to the peculiarities of life of local communities.